Single-molecule Studies of RNA Polymerase: Motoring Along - Herbert, Kristina M. (2008)
Single-molecule techniques have advanced our understanding of transcription by RNA polymerase. A new arsenal of approaches, including single-molecule fluorescence, atomic-force microscopy, magnetic tweezers, and optical traps have been employed to probe the many facets of the transcription cycle. These approaches supply fresh insights into the means by which RNA polymerase identifies a promoter; initiates transcription, translocates and pauses along the DNA template, proofreads errors, and ultimately terminates transcription. Results from single-molecule experiments complement knowledge gained from biochemical and genetic assays by facilitating the observation of states that are otherwise obscured by ensemble averaging, such as those resulting from heterogeneity in molecular structure, elongation rate, or pause propensity. Most studies to date have been performed with bacterial RNA polymerase, but work is also being carried out with eukaryotic polymerase (Pol II) and single-subunit polymerases from bacteriophages. We discuss recent progress achieved by single-molecule studies, highlighting some of the unresolved questions and ongoing debates.